Clown nose: views about the documentary “Achei o meu nariz [I’ve found my nose]” - Guimarães, Gleuter Alves; Almeida Nunes, André; Silva, Roberta Machado (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This article proposes a collective reflection on the documentary “Achei o meu nariz” (I’ve found my nose), which tells the story of a journey through the world of female clowning, presenting the trajectories, difficulties and achievements of the clowns from the groups “As Marias da Graça”, “Casa 407” and “Palhaça Catha Vento”. This analysis discusses, from the perspective of Cultural Performances, the construction of the figure of the women clowns and the related aspects between the way they tell their own stories and the narrative language of documentary cinema. The goal is to find an approach that establishes a common dialogue between the research of the three observers, creating a connection between different layers of analysis under the same cultural product.